If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 194 + -2x = 43x + 19 Reorder the terms: 194 + -2x = 19 + 43x Solving 194 + -2x = 19 + 43x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-43x' to each side of the equation. 194 + -2x + -43x = 19 + 43x + -43x Combine like terms: -2x + -43x = -45x 194 + -45x = 19 + 43x + -43x Combine like terms: 43x + -43x = 0 194 + -45x = 19 + 0 194 + -45x = 19 Add '-194' to each side of the equation. 194 + -194 + -45x = 19 + -194 Combine like terms: 194 + -194 = 0 0 + -45x = 19 + -194 -45x = 19 + -194 Combine like terms: 19 + -194 = -175 -45x = -175 Divide each side by '-45'. x = 3.888888889 Simplifying x = 3.888888889
| 24x^2+24x=0 | | 27+(4x-30)+(3x-10)+x=360 | | 4(1)-5y=9 | | a^3+7a^2+12a+24= | | 6x^2-9x-105=0 | | 15=200 | | -3x+4y=21 | | -10x+6y=-2(3-y) | | 65-131=11(x-1) | | x-11=-3-20 | | -2x=-6y+9 | | 11x-10x=8x+5 | | x+3=-28+10 | | 4a^2+2.25a+1=0 | | (x+8)(x)(x-2)=96 | | 3x/2+6x/5=5+x/5 | | 5z-z=5-37 | | x-42=48 | | 6v^2-9v-60=0 | | (x+4)(x)(x-2)=96 | | -20x=-10 | | 4x^2-24x+32= | | 2q+b=c | | 12-2x+3x-5-7x= | | 1x=5+0.75x | | 3.5x^7+4.5x^6-2.5x^2+4x=0 | | 42.75=4.75*x | | 75+0.10=400 | | 75+.10=400 | | log(5x+1)+log(2)=Log(9x+10) | | 25.25=1.75*x | | 19=-2x-1 |